2003
DOI: 10.1074/jbc.m306534200
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Interaction between Ribosomal Proteins S7 and S11 within the Bacterial Ribosome

Abstract: In this study, we used site-directed mutagenesis to disrupt an interaction that had been detected between ribosomal proteins S7 and S11 in the crystal structure of the bacterial 30 S subunit. This interaction, which is located in the E site, connects the head of the 30 S subunit to the platform and is involved in the formation of the exit channel through which passes the 30 S-bound messenger RNA. Neither mutations in S7 nor mutations in S11 prevented the incorporation of the proteins into the 30 S subunits but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 72 publications
(71 reference statements)
2
44
0
1
Order By: Relevance
“…The reduced binding of eEF3 to mutant ribosomes, which favors binding of cognate aminoacyltRNA at the A-site (Uritani and Miyazaki 1988) may also contribute to altered translational fidelity. A similar effect has been previously observed in the case of mutations in E. coli rpS7 (the bacterial rpS5 homolog), which disrupted its interaction with rpS11 (Robert and Brakier-Gingras 2003). The authors likewise suggested that mutations in rpS7 might have impaired the coupling between the E-and the A-site and that this contributed to the reduced translation fidelity (Robert and …”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…The reduced binding of eEF3 to mutant ribosomes, which favors binding of cognate aminoacyltRNA at the A-site (Uritani and Miyazaki 1988) may also contribute to altered translational fidelity. A similar effect has been previously observed in the case of mutations in E. coli rpS7 (the bacterial rpS5 homolog), which disrupted its interaction with rpS11 (Robert and Brakier-Gingras 2003). The authors likewise suggested that mutations in rpS7 might have impaired the coupling between the E-and the A-site and that this contributed to the reduced translation fidelity (Robert and …”
Section: Discussionsupporting
confidence: 69%
“…1A; Yusupov et al 2001;Spahn et al 2004) and cross-links to the E-site tRNA (Wower et al 1993;Doring et al 1994). rpS7 also contributes to the formation of the so-called mRNA exit channel and interacts with rpS11, which is located on the platform of the 30S subunit (Robert and Brakier-Gingras 2003). This interaction was suggested to contribute to the structural rearrangements of the head of the 30S subunit during translation (Robert and Brakier-Gingras 2003).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations